Why are Certain Students Further from Achieving Their Desired Level of English Proficiency? - Fëllanza CANOLLI MALLET (Prizren Social Science Journal)
This study deals with proficiency of students towards English Language Learning. It includes ELT strategies that can properly motivate students to learn the language without betraying where they come from. Although many of them are afraid that learning English might assimilate them, therefore, they hesitate to learn English due to their Educational system which makes them fearful of losing their identity.